A survey on the preference of dentists in Manila in the use of either the chisel and mallet or surgical burs for the removal of impacted mandibular third molars - De Jesus, Sarah; Parlan, Elaine Margaret; Gervasio, Natividad (Adviser).
A survey of 288 dentists who are listed as members of the PDA - Manila Chapter was undertaken to determine which of the chisel and mallet and surgical bur do most dentists in Manila prefer to use for the removal of impacted mandibular third molars and whether there was a relation between the number of years a dentist has been practicing and his preference for either. Respondents who had less than twenty (20) impaction cases were eliminated and the remaining were grouped according to the number of years they have been practicing. Results show that out of the seventy-two (72) who qualified for the study, fifty-four (54) of seventy-five (75) percent preferred surgical bur and eighteen(18) or twenty-five(25) percent preferred chisel and mallet. The primary reasons for the preference for the surgical bur are less apprehension and trauma on patients and less time consuming and for the chisel and mallet, faster procedure and less trauma and laceration to tissue. The survey also showed that no relation exists between the number of years a dentists has been practicing and his preference as interpreted from the statistical test - Chi square that was done.
Seminar Paper--Doctor of Dental Medicine--University of the Philippines Manila.
Keywords: Dental instruments and apparatus